GUT CONTENT ANALYSIS OF Terapon jarbua FROM THE VIZHINJAM COAST OF SOUTH INDIA - THOMAS, ANCY; MANJU, K. G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Food plays an important role in the growth, development and reproduction of fishes. The nature of food content in the gut helps to understand the ecology and trophodynamics of the fish. The present study is an attempt to identify the gut contents of Terapon jarbua collected from the Vizhinjam Coast of South India. The different food items in the gut of the fish collected for a period of one year were identified and grouped in to 10 different categories. Monthly variation in the percentage composition of the gut contents were assessed. The food components in the gut of male fish were in the order: Sand > Digested matter > Miscellaneous > Fish > Bivalves > Crustaceans > Gastropods > Polychaetes > Phytoplankton > Zooplankton. The composition of gut contents of female fishes followed the order: Polychaetes > Crustaceans > Miscellaneous > Digested matter > Sand > Fish > Phytoplankton > zooplankton > Bivalve > Gastropods. The feeding intensity and food preferences varied monthly and Crustaceans were found to be the most dominant food item in the diet. Gastro somatic index indicated decline during the monsoon months. The study indicated that Terapon jarbua is a euryphagous fish with broad feeding habits.